BER Performance of Ultra-Wideband Signal in Optical Transmission Line - Gwo Chin, Chung; Chu Liang, Lee; Zheng Yang, Lim; It Ee, Lee (International Journal of Engineering and Technology, 2018)
The main interest of ultra-wideband (UWB) system is that it can coexist with the current radio system with minimal or no interference, which indeed benefits the radio service provider to avoid paying expensive spectrum licensing fees. However, UWB system has a limited propagation distance, typically up to 10 meters. Thus, optical UWB technology has been proposed recently to overcome this problem. In this paper, Matlab simulation has been done to study the performance of the UWB signal in the optical transmission line. Bit error rate (BER) performance has been compared using minimum mean square error (MMSE) equalizer with varying tap length. Results indicate that the distance of the UWB signal transmission can be extended using optical fibre as long as the sampling rate does not cause the optical multipath channel to generate too much interference.Â Â